2011
DOI: 10.1111/j.1365-2745.2011.01883.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits shape ontogenetic growth trajectories of rain forest tree species

Abstract: Summary1. Functional traits are posited to explain interspecific differences in performance, but these relationships are difficult to describe for long-lived organisms such as trees, which exhibit strong ontogenetic changes in demographic rates. Here, we use a size-dependent model of tree growth to test the extent to which of 17 functional traits related to leaf and stem economics, adult stature and seed size predict the ontogenetic trajectory of tree growth. 2. We used a Bayesian modelling framework to parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
231
3
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 202 publications
(267 citation statements)
references
References 55 publications
26
231
3
7
Order By: Relevance
“…We confirmed that the vigor index is negatively related to mortality: trees that grow more than expected have a lower probability of dying, and trees with lower-thanexpected growth have a higher probability of dying. Moreover, the posterior values for obtained the functional trait parameters are coherent with results of Hérault et al (2011) and Aubry-Kientz et al (2013), increasing our confidence in (i) the developed algorithm and (ii) the biological determinism of the ecological processes we want to model. This confirms that the functional trait-based approach could be successfully used to predict climate-induced tree dynamics in highly diverse tropical forests for which taxonomic data may be lacking but functional trait data are available.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We confirmed that the vigor index is negatively related to mortality: trees that grow more than expected have a lower probability of dying, and trees with lower-thanexpected growth have a higher probability of dying. Moreover, the posterior values for obtained the functional trait parameters are coherent with results of Hérault et al (2011) and Aubry-Kientz et al (2013), increasing our confidence in (i) the developed algorithm and (ii) the biological determinism of the ecological processes we want to model. This confirms that the functional trait-based approach could be successfully used to predict climate-induced tree dynamics in highly diverse tropical forests for which taxonomic data may be lacking but functional trait data are available.…”
Section: Discussionmentioning
confidence: 81%
“…Life-history strategies describe how trees allocate resources to different organs and how these allocations translate into a species' ability to compete for resources and finally to grow, survive, reproduce and disperse (Rüger et al, 2012). Some of these functional traits are accurate proxies of growth trajectories (Herault et al, 2010;Hérault et al, 2011) and mortality rates .…”
Section: Functional Traitsmentioning
confidence: 99%
“…2, β 1 ). The link between traits and average survival is not surprising given that the traits that we studied are closely associated with resource acquisition, storage, and defense (32,33,35,(39)(40)(41). Among the traits considered, WSG was the strongest predictor of species average survival, independent of variation in neighborhood crowding.…”
Section: Discussionmentioning
confidence: 94%
“…The data sets collated fell into two broad categories: (1) national forest inventories (NFI), in which trees above a given diameter were sampled in a network of small plots (often on a regular grid) covering the country (references for NFI data used [39][40][41][42][43][44][45][46][47][48] ); (2) large permanent plots (LPP) ranging in size from 0.5 to 50 ha, in which the x-y coordinates of all trees above a given diameter were recorded (references for LPP data used refs [49][50][51][52][53][54][55][56]. LPP were mostly located in tropical regions.…”
Section: Model and Analysismentioning
confidence: 99%